2015
DOI: 10.1007/s00586-015-3796-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of vascular complications during lateral lumbar interbody fusion: an examination of the mini-open access technique

Abstract: The mini-open lateral access technique for LLIF provides for minimal risk of vascular injury to the lumbar spine. In the rare event of minor vascular injury, the mini-open access approach allows for immediate visualization, confirmation and repair of the vessel with no long-term sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Using an identical oblique lumbar interbody fusion technique, Silvestre et al [44] reported a vascular complication risk of 1.68% including iliac and iliolumbar venous lacerations. These results are comparable to those for far lateral approaches such as the extreme lateral transpsoas approach, which were developed specifically to avoid vascular injury, and which range from 0% to 0.11% in large case series [22,40]. All three vessel lacerations in our series involved the L4-L5 segment, and we recommend careful and meticulous preparation and more posterior dissection of the anterior border of the psoas muscle.…”
Section: Discussionsupporting
confidence: 77%
“…Using an identical oblique lumbar interbody fusion technique, Silvestre et al [44] reported a vascular complication risk of 1.68% including iliac and iliolumbar venous lacerations. These results are comparable to those for far lateral approaches such as the extreme lateral transpsoas approach, which were developed specifically to avoid vascular injury, and which range from 0% to 0.11% in large case series [22,40]. All three vessel lacerations in our series involved the L4-L5 segment, and we recommend careful and meticulous preparation and more posterior dissection of the anterior border of the psoas muscle.…”
Section: Discussionsupporting
confidence: 77%
“…This tubular dilator based technique has recently been modified to a single incision mini-open access technique, which is utilized at our institution. This technique allows for direct visualization of retroperitoneal and neural structures, digital palpation of the target disc as well as electrophysiological neurologic confirmation during the procedure [26]. Our institution's experience regarding sensorimotor complications and vascular injuries using the mini-open access technique has previously been published [26][27][28][29].…”
Section: Evolution Of the Techniquementioning
confidence: 99%
“…The overall incidence of vascular injury at our institution using LLIF is 0.056% per case and 0.029% per level. The mini-open access technique has been shown to be useful for immediate repair of minor vascular injuries [26]. Although rare, potentially lethal major vascular complications during LLIF are possible.…”
Section: Vascular Injurymentioning
confidence: 99%
See 2 more Smart Citations